National poet and destiny of the nation. (Eurasian Journal of Philology Science and Education, 2015)
In the article the accord of thoughts of poets "Grief eras" with ideas of national pedagogics reveals. Along with it, the author points to how poets of this period, having precisely guessed trend of that era, truthfully represented its reality.The researcher also pays special attention to that in poetic creativity of representatives of that era who have described the tragedy and sorrows of the people, compelled to obey to policy of colonization, national ideas andnational attitude found reflection. Especially brightly and comprehensively it is expressed by means of unusual comparisons, thoughtful images and comparisons.
Keywords: grief era; customs; national attitude; meter; traditions; education